Malaysian’s consumers’ preferences in purchasing pineapples: case study in Jasin, Melaka / Shaflk Bansan and Nabila Huda Aziz - Bansan, Shaflk; Aziz, Nabila Huda (Faculty of Plantation and Agrotechnology, 2018)
Pineapples or Ananas Comusus from the family Bromeliaciae was a plant in which tropical!}'origin from east Area of South America. Pineapple was started worldwide production by 15thcentury. Malaysia was well known as one of the world pineapple suppliers. Malaysia was the 18thtop production pineapple in the world and the production of pineapple about 391714 a year. Theobjectives of this study was to determine the factors of Malaysian’s consumers’ preference inpurchasing. From the factors, this study is to evaluate the most dominant factor of Malaysian'sconsumers’ preferences in purchasing pineapples. A total of 200 respondents from Jasin. Melakawith objectives of identifying factors affecting Malaysian’s consumer’s preferences purchasingpineapple in the study area. Respondent were asked about demand toward pineapples, knowledgelevel on pineapples, characteristic of pineapples and consumer preferences purchasing pineapples.The obtained data were analysed using descriptive analysis and exploratory factor analysis. Fromthe result KMO, 0.721 was reliable acceptable for conducting factor analysis since it w as greaterthan 0.5. From factor analysis, the result illustrated that, the demand was the most dominantattribute towards Malaysian's consumers’ preferences in purchasing pineapples. ]t was representedby three main factors which eigenvalues more than 1. no trouble eating pineapples (3.942).acceptable pineapples (2.602) and purchasing pineapples (2.092). It was about 57.6 % of totalvariance w ere explained by three factors. From this result, it w'as proven that the consumer demandindirectly can increase pineapples production.